Penggunaan Sumber Otoritas Keilmuan Qaul Ulama’ dalam Fatwa DSN-MUI - Muhammad Fakhril Umam Fakhri; Roisul Umam Arrasyidi Rois; Aji Saifullah Aji; Dhika Tabrozi Dhika (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2026)
The National Sharia Council of the Indonesian Ulama Council (DSN-MUI) plays a vital role in the development of Islamic economics in Indonesia by issuing fatwas that serve as guidelines for Islamic financial institutions. This study aims to analyse the epistemological framework of DSN-MUI fatwas, with a focus on the qauli approach and the schools of Islamic jurisprudence (Madhhabs) utilised in the legal reasoning (istinb??) process. Employing a qualitative methodology that combines library research and descriptive-analytical analysis, this research applies an epistemological framework to identify and classify the opinions (qaul) of scholars cited in DSN-MUI fatwas. These opinions are categorised according to the scholars’ Madhhab affiliations, historical periods, and methodological characteristics. The findings indicate that the DSN-MUI employs a cross-Madhhab approach, drawing upon scholars from various schools of thought (Hanafi, Maliki, Shafi‘i, Hanbali, and Zahiri), as well as contemporary scholars. The epistemological framework of DSN-MUI fatwas is integrative, combining the legacy of classical fiqh with contemporary ijtihad and a maq??id-based perspective to address the challenges of modern Islamic economic practices.